Cancer Screening in Patients with End-Stage Renal Disease: An Individualized Approach. Issue 1 (January 2017) - Rosner, Mitchell H.
Cancer screening guidelines exist for the general population with the expectation that screening will improve health outcomes. However, such recommendations are not easily or appropriately generalized to the end-stage renal disease (ESRD) population where mortality is high and life expectancy is often less than 5 years. Furthermore, the operational characteristics of screening tests in the ESRD population are not the same as in the general population, which changes their predictive value. Thus, an individualized approach to cancer screening is warranted in patients with ESRD, which balances the life expectancy and the potential benefits from screening versus potential costs and harm.